GOOD GOVERNANCE SEBAGAI MODEL RETORIS - Teguh Priyo Sadono (Bricolage : Jurnal Magister Ilmu Komunikasi, 2016)
Throughout the history of the state of life, a nation are always colored tidal beliefs of the management of the State. Various approaches are used through policy model be pursued in the conception of the ideal model of building a nation in achieving its goals. Start with the assumption state approach as an effective phrase, shifted to Market and civil society did not obtain a formula that considered the most effective. Then came the views of good governance is regarded as a dynamic view and dialectics approach in the management of government supervision. However, in the implementation of global factors strongly influence national policy models, So Good Governance merely a rhetorical concept that can not be applied in empirical level. Keywords: approaches, state, market, civil society, Governance